The didactic track game as a geography teaching strategy - Miranda, Marcelo Ricardo Bezerra de; Vieira, João Luiz da Silva (Geosaberes; Vol 10 No 22 (2019): Sept - DecDO - 10.26895/geosaberes.v10i22.803, 2019)
The education deals with challenges such as the need to develop more dynamic and participative classes, facing a world with so much technological information available, the expositives classes are not attractive to the students. In this scenario it was formulated a didactic game in track format, a game very used by the teenagers, aiming to analyze the impact of this resource in the geography classes. The theme chosen to produce the games was the geological time and the Brazilian morphoclimatic domains. It was presented to the students that didn’t studied the theme before and to others that already did, considering in this way to be able to compare the results and evaluate the viability. After participation in the game, they showed receptivity and argumented that this strategy is a potential means for teachers to make their classes participative and viability ways to the concretization of the learning.